PENGARUH KESADARAN WAJIB PAJAK, SANKSI PAJAK, PENGETAHUAN PERPAJAKAN DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KABUPATEN ACEH TENGGARA - Alfriado Leonard Noprian Dolok Saribu; Lolo Violenta Keterina; Indah Cahya Sagala; Muhammad Habibie (Multidisciplinary Indonesian Center Journal (MICJO), 2024)
Taxes are the main source of government and state revenue used to finance government spending and national development. This research aims to examine the effect of taxpayer awareness,tax penalties, tax knowledge, tax service quality to the taxpayers compliance of motor vehicles in District Southeast Aceh. The population used in this study is taxpayers who own motorized vehicles registered at the SAMSAT Office in Southeast Aceh Regency. The number of samples in this study were 100 respondents with the sampling method using the Simple Random Sampling technique. The data used in this study is primary data from the result of distributing questionnaires. The test method uses the Valadity and Reliability test, Classical Assumption test, and Multiple Regression Analysis with the SPSS for Windows Version 25 program. The results of this study found that the variables of Taxpayes Awareness, Tax Sanctions, Tax Knowledge and Fiscus Services have a positive and significant effect on Motor Vehicle Taxpayer Compliance in District Southeast Aceh. With the result of this study it is hoped that the Southeast Aceh District SAMSAT office will continue to improve its performance so that people have confidence in paying taxes